2008
DOI: 10.1248/bpb.31.1131
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Activity of Derivatives of Ouabain, Digoxin and Proscillaridin A in Human MCF-7 and MDA-MB-231 Breast Cancer Cells

Abstract: Three derivatives of ouabain, digoxin and proscillaridin A containing the carboxylic group instead of the lactone moiety were synthesized and examined for cytotoxicity in human breast cancer cells. Evaluation of the cytotoxicity of these compounds employing an MTT assay and inhibition of [ 3 H]thymidine incorporation into DNA in both MCF-7 and MDA-MB-231 breast cancer cells demonstrated that compound 3, the most active of the series, proved to be only slightly less potent than proscillaridin A. We evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
53
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 34 publications
4
53
1
Order By: Relevance
“…However, the dramatic fall in this activity over longer-term suggests that there could be two populations within the cell line, only one of which is sensitive to the caspase-3 pathway. As previously described, MDA-MB-231 cells can activate the caspase-3 pathway via polyunsaturated fatty acids (19). Thus, early activation of this enzymatic activity, resulting in the rapid death of this population, would be compatible with the fall in cell number observed in Fig.…”
Section: Discussionsupporting
confidence: 74%
“…However, the dramatic fall in this activity over longer-term suggests that there could be two populations within the cell line, only one of which is sensitive to the caspase-3 pathway. As previously described, MDA-MB-231 cells can activate the caspase-3 pathway via polyunsaturated fatty acids (19). Thus, early activation of this enzymatic activity, resulting in the rapid death of this population, would be compatible with the fall in cell number observed in Fig.…”
Section: Discussionsupporting
confidence: 74%
“…Other investigators found that ouabain and digoxin selectively induced apoptosis in a human acute T-cell lymphoblastic leukemia cell line [2]. In the estrogen dependent/independent breast cancer cell lines, CS similarly exerted antiproliferative effects, suggesting their potential use as anticancer agents [7].…”
mentioning
confidence: 95%
“…Ouabain could induce HepG2 cell apoptosis and generate S phase arrest, and siRNA could enhance the anti-cancer effect of ouabain that induced HepG2 cells apoptosis via an intracellular Ca 2؉ ؉ and ROS increase-mediated, and generated cell cycle S phase arresting by decreasing the CyclinA1/cyclin-dependent kinase 2 (CDK2)/proliferating cell nuclear antigen (PCNA) complex product and increasing the expression of cyclin-dependent kinase inhibitor 1A (P21 tive oxygen species (ROS) by mitochondria. 12) We believe that ouabain can induce DNA double strand breaks by increasing the intracellular free Ca 2ϩ and ROS concentrations. In China, HCC ranks 3rd in terms of the mortality rate of malignant tumors.…”
mentioning
confidence: 98%
“…Previous research has shown the Na ϩ /K ϩ -ATPase a1 subunit was highly expressed in malignant cells, including human prostate cancer PC-3, DU-145 cells, human non-small cell lung cancer (NSCLC) A549 cells, 10) glioblastomas Hs683, U373-MG, U87-MG, T98G cells, 11) and breast cancer MCF-7 cells. 12) Mijatovic found that cell invasion and proliferation were significantly reduced after knockdown of the Na ϩ /K ϩ -ATPase a1 subunit expression in NSCLC (A549) cells. 13) These findings indicated that the Na , which provides the driving force for the transport of other solutes, notably amino acids, sugars, and phosphate.…”
mentioning
confidence: 99%